2022
DOI: 10.1136/jmg-2022-108653
|View full text |Cite
|
Sign up to set email alerts
|

Patient-facing digital tools for delivering genetic services: a systematic review

Abstract: This study systematically reviewed the literature on the impact of digital genetics tools on patient care and system efficiencies. MEDLINE and Embase were searched for articles published between January 2010 and March 2021. Studies evaluating the use of patient-facing digital tools in the context of genetic service delivery were included. Two reviewers screened and extracted patient-reported and system-focused outcomes from each study. Data were synthesised using a descriptive approach. Of 3226 unique studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…In addition to aligning with others’ findings that some are hesitant to use chatbots in healthcare due to accuracy concerns and a lack of empathy (Nadarzynski et al 2019 ), our work expands the evidence base (Lee et al 2022 ) to include details about patients’ and parents’ preferences for key functions and use cases. Since the acceptability of chatbot use may depend on the clinical indication for genetic testing or the acuity of the situation (e.g., during the newborn period), ongoing preference research in real-world clinical settings is warranted.…”
Section: Discussionsupporting
confidence: 60%
“…In addition to aligning with others’ findings that some are hesitant to use chatbots in healthcare due to accuracy concerns and a lack of empathy (Nadarzynski et al 2019 ), our work expands the evidence base (Lee et al 2022 ) to include details about patients’ and parents’ preferences for key functions and use cases. Since the acceptability of chatbot use may depend on the clinical indication for genetic testing or the acuity of the situation (e.g., during the newborn period), ongoing preference research in real-world clinical settings is warranted.…”
Section: Discussionsupporting
confidence: 60%
“…A systematic review reported there are at least 70 different tools for delivering genetics care, including web-based portals, applications, and digital tools that may be used for clinical assessment, patient education, pretest and posttest counselling, and reporting results. 18 Should some of these (or future) digital tools see increasing adoption and implementation over the next 5 years, they will likely raise several opportunities and considerations for health systems. For example, amid increasing demand for genetic testing, these technologies could help improve access to patient counselling services delivered by clinical geneticists, genetic counsellors, or primary care providers.…”
Section: Top Precision Medicine Technologies To Watchmentioning
confidence: 99%
“…17 Some digital technologies may improve workflow efficiencies by reducing administrative time spent preparing charts or other materials. 18 Similar to the broader digital health space, the growth prospect of digital tools for genetics underscores the growing importance of patient data privacy and security, which are key concerns for people in Canada. 19 Continuing to enhance data privacy infrastructures will be pertinent for addressing safety concerns, as genetic test results from medical records will need to connect seamlessly with patient-facing digital tools while still ensuring sensitive information, such as genetic risk factors, remains secure and confidential.…”
Section: Top Precision Medicine Technologies To Watchmentioning
confidence: 99%
“…Digital genomic tools are often developed and tested across non-diverse populations, with limited consideration of various end-users and communities, or their unique cultural, educational, and accessibility needs. These patient-facing tools are primarily developed and evaluated by English-speaking individuals of highly educated, White backgrounds [4,[6][7][8]. This lack of diversity among participants in the upfront design of these tools limits the inclusion of varied needs and perspectives of diverse populations and may serve to widen digital health inequities further [9].…”
Section: The Lack Of Diversity Considerations In the Development Of D...mentioning
confidence: 99%